Effect of sowing dates and nutrient sources on nutrient uptake of Indian mustard (Brassica juncea) - KUMAR, SUNIL; MEENA, RAM SWAROOP; JATAV, SURENDRA SINGH (The Indian Journal of Agricultural Sciences, 2020)
In India, people facing malnutrition due to soil and environmental problems. Keeping in mind these problems, a field experiment was conducted during rabi season of 2015 and 2016 at Agricultural Research Farm, Institute of Agricultural Sciences, BHU, Varanasi. The aim of study was to use the combination of pressmud (PM) as organic source of nutrient and recommended dose of fertilizer (RDF) with different sowing dates on Indian mustard (Brassica juncea (L.) Czernj. & Cosson). The experiment laid out in the split-plot design with 24 treatments combinations, viz. three sowing dates in main plot treatment–(November 17, November 27, December 7), and eight nutrient sources in sub-plots, viz. Control, 100% RDF, 100% RDF + Azotobacter, 100% RDF + Phosphorus solubilizing bacteria (PSB), 100% RDF + Azotobacter + PSB, 75% RDF + 25% N through PM+ Azotobacter, 75% RDF + 25% N through PM + PSB, 75% RDF + 25% N through PM + Azotobacter + PSB. The results found that the crop sowing on November 17, total nitrogen uptake was recorded 103.31 kg ha-1. Likewise, total phosphorus, potassium and sulphur uptake was recorded 33.73, 87.38 and 16.83 kg ha-1, respectively on the basis of pooled analysis as compared to other crop sowing on November 27 and December 7. Among the nutrient sources application of 75% RDF + 25% N through PM +Azotobacter + PSB maximum total nitrogen, phosphorus, potassium and sulphur uptake was recorded on the basis of pooled analysis as compared with other nutrient sources.